Pendampingan dan Pembuatan Nomor Induk Berusaha melalui Online Single Submission bagi Para Pelaku UMKM Desa Laweyan - Ayu Sabrina; Taufikurrahman; Rachmad Rifqi Alamsyah (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2022)
Micro, Small and Medium Enterprises (MSMEs) in Probolinggo are growing quite rapidly. Laweyan Village, which is one of the villages in Sumberasih District, which has quite a number of MSME actors. MSME actors need a permit as proof that the business does exist, operates, and is worthy of standing. The permit functions to foster, direct, supervise, and regulate the business activities carried out. Based on observations made of MSME actors in Laweyan, not all business actors have business legality. Some of the obstacles that cause business actors not to have a business license include: (1) not knowing the benefits that will be obtained by having a business license, (2) finding it difficult when applying for a license, and (3) not understanding how to apply for a business license. Mentoring activities are divided into 3 stages, namely distribution of socialization invitations, mentoring, and submission of NIB. Based on the data obtained, MSME actors are divided into 3 types of risk, so that in the future we can easily direct them to a better direction.